Postawy duchowieństwa katolickiego wobec systemu komunistycznego w województwie łódzkim w latach 1948–1956. Zarys problemu - Stefaniak, Janusz (Acta Universitatis Lodziensis. Folia Historica, 2015)
The present publication concerns Catholic clergy attitudes towards communist system in Lodz Voivodeship. From the very beginning of change of political system in 1944 members of clergy were submitted to various forms of forcing them to be politically loyal and ready to cooperate with the authorities. The undertaken research leads to a conclusion that the opinion promoted by contemporary propaganda presenting attitudes among the clergy as mostly positive does not seem to be so certain. In Lodz Diocese passive and moderate feelings certainly dominated, as well as those of awaiting. Not uncommon were disapproving or even hostile attitudes towards the new system, authorities, directives and decrees passed. Positive attitudes were rare. Year 1956 only partly restricted the repressive policy of the authorities towards the clergy.